Teoria braku teorii. Jak można pisać o teorii w architekturze polskiej po 1945 roku? - Jędruch, Dorota (Artium Quaestiones, 2025)
This article grew out of the experience of working on the publication “Texts of Modernism. An Anthology of Polish Theory and Criticism of Architecture 1918-1981” (eds. D. Jędruch, M. Karpińska, D. Leśniak-Rychlak, Kraków 2018). The book was a pioneerTeoria braku teorii. Jak można pisać o teorii w architekturze polskiej po 1945 roku? 63 ing attempt in Polish historiography of architecture to compile a set of source texts on the theory and criticism of 20th-century architecture. The considerations primarily concerned sources created after 1945 and involved selecting those source materials in the book and analysing specific features of “text anthology” as a scientific genre, situating anthologies between the academic research and didactic or popularizing goals of the study. The essay proposes several analytical tropes in organising the source material: criteria and conditions for classifying a text as a “theory of art”, discourse analysis, media research methods and visual culture studies, which can be a useful tool for researching architectural publications. One of the main concerns of the text is the conviction about the “lack of theory” and “lack of theory of architecture” in Poland after 1945, which was expressed in many of the materials analysed, while texts taking up theoretical issues and discussing current trends in architecture were very numerous in this period in Poland. This article attempts to answer the question of where this conviction about the “lack of theory” stems from and how it relates to possible attempts to create a “canon” of source texts. The text also asks about the role of synthetic studies of anthologies of source texts for the historiography of architecture.